2012
DOI: 10.1002/jcb.23381
|View full text |Cite
|
Sign up to set email alerts
|

Glycosilated nucleolin as marker for human gliomas

Abstract: Nucleolin is a multifunctional DNA and RNA binding protein involved in regulation of gene transcription, chromatin remodeling, RNA metabolism, and ribosomal RNA synthesis. Nucleolin seems to be over-expressed in highly proliferative cells and is involved in many aspect of gene expression: DNA recombination and replication, RNA transcription by RNA polymerase I and II, rRNA processing, mRNA stabilization, cytokinesis, and apoptosis. Although nucleolin is localized predominantly in the nucleolus, it has also bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 36 publications
3
49
0
3
Order By: Relevance
“…Recently, nucleolin was also found to be present on the cell surface in a wide range of cells (Galzio et al, 2012) and serve as receptors for HIV-1, ECM, adhesion molecules and growth factors Wang et al, 2011). Consistent with these reports, our results showed that nucleolin exists in the membrane fraction of A375 cells (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, nucleolin was also found to be present on the cell surface in a wide range of cells (Galzio et al, 2012) and serve as receptors for HIV-1, ECM, adhesion molecules and growth factors Wang et al, 2011). Consistent with these reports, our results showed that nucleolin exists in the membrane fraction of A375 cells (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Nucleolin over expression is related with increased cell proliferation. Cell surface nucleolin is found in a wide range of tumor cells, and it is used as a marker for cancer diagnosis [15, 16]. Increased levels of cytoplasmic and cell-surface nucleolin have been demonstrated to correlate with malignancy grade and proliferation rate in glioblastoma [15].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the phosphorylated Smad complex is linked into Smad4 and then shuttled into the cell nucleus, where the complex initiates the corresponding gene transcription and protein expression [6][7][8]. At the same time, C23 protein is reported to express in the different subcellular structures of cancer cell [9][10][11], such as colorectal cancer [12] and gliomas [14]. Notably, C23 is demonstrated to influence some receptor-mediated signaling pathways [15].…”
Section: Introductionmentioning
confidence: 96%